Epidemiological Survey on Edentulousness in Elderly Nepalese Population - Basnyat, S KC; Sapkota, B; Shrestha, S (Kathmandu University Medical Journal, 2015)
Background A lot of epidemiological surveys have been conducted in dental caries and periodontal problems, but prosthetic sector is lacking such study.Objective The aim of this study was to assess the level of edentulousness, the cause of edentulousness, the denture wearing and denture needs of selected Nepalese population. It will also analyze how factors, such as habits, built, educational needs influence edentulousness.Method Patients visiting the Dental Outpatient Department of Dhulikhel Hospital and various dental camps organized by the hospital were selected for study. The examination was conducted using basic diagnostic tools (Mouth mirror, straight probe and explorer). Statistical software SPSS 16.0 was used for data analysis, chi-square test was performed for each parameter.Result The statistical analysis showed that age was statistically associated to edentulousness, but gender and built were not associated to edentulousness. Furthermore educational status and habit were statistically associated with edentulousness.Conclusion Oral health awareness and education programs should be conducted at the community level for every individual. The role of oral hygiene practice, the negative effect of various oral habit, especially smoking and tobacco chewing habits, the need to replace missing teeth and care of artificial denture should be explained.Kathmandu University Medical Journal Vol.12(4) 2014; 259-263